PENGUATAN LITERASI KEAGAMAAN ISLAM MODERAT BAGI PESERTA DIDIK - Ali Ahmad Yenuri (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
Abstract: This paper examines the strengthening of moderate Islamic religious literacy for students. The strengthening is very important because of the many intolerant and extreme religious understandings. In many ways, this understanding is caused by the low literacy ability of students. Therefore, the author wants to show the literacy of moderate Islamic religion as a solution to these misunderstandings. The first study focused on studying the concept of Islamic religious literacy. Subsequent studies were conducted to find a comprehensive meaning regarding moderate Islam. Here, the author also presents strategies to developing literacy skills that can be done by teachers in educating their students. These skills can be developed with the seven stages i.e. reflection, inquiry, empathy, analysis and evaluation, reasoning, synthesis and communication.Keywords: Religious Literacy, Moderate Islam, and Literacy Skills.